The effect of equipment scaling on children`s sport performance: the case for tennis - Timmerman, E.; De Water, J.; Kachel, K.; Reid, M.; Farrow, D.; Savelsbergh, G. (Journal of Sports Sciences, 2015)
The influence of scaling court-size and net height on children`s tennis performance was examined. Sixteen boys (9.7 ± 0.5 years) had to perform a 30-min match in four different conditions, where court-size and/or net height were scaled by using a scaling ratio based on the differences in temporal demands between the children and the adult game. These 30-min matches were analysed using Tennis Analyst (FairPlay Ltd., Jindalee, QLD, Australia) software to determine typical tennis match performance characteristics. Children hit more winners, more forced errors, played more volleys, struck more shots from a comfortable height and played in a more forward court position when the net was scaled. Scaling both the court and net lead to a faster children`s game, more closely approximating what is typical of the adult game. The differences between the typical tennis performance variables recorded suggested that scaling the net led to a more aggressive way of playing. Further, children enjoyed playing on the standard court-scaled net condition more than standard adult conditions. It is suggested that optimising the scaling of net height may be as critical as other task constraints, such as racquet length or court-size, as it leads to a more engaging learning environment for experienced children.